2018
DOI: 10.1002/mp.12803
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive evaluation of broad‐beam transmission of patient supports from three fluoroscopy‐guided interventional systems

Abstract: This study evaluated the broad-beam transmission for three representative fluoroscopy systems and their dependency on angle, kVp, added Cu filter, and field size. The comprehensive data provided for patient support transmission will facilitate accurate calculation of peak skin dose (PSD) and may potentially be integrated into real-time and retrospective dose monitoring with access to Radiation Dose Structured Reports (RDSR) and radiation event data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Although this was corrected using BPMMAst, human patients are comprised of soft tissue, bone, and air, and a more thorough investigation of the scattering properties of these materials would be helpful to estimate skin dose more accurately. Another limitation was the use of a single support pad for both systems; previous work has shown a relationship between TTF and support pad thickness . Vendors typically quote the equivalent aluminum thickness (mm Al Eq.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this was corrected using BPMMAst, human patients are comprised of soft tissue, bone, and air, and a more thorough investigation of the scattering properties of these materials would be helpful to estimate skin dose more accurately. Another limitation was the use of a single support pad for both systems; previous work has shown a relationship between TTF and support pad thickness . Vendors typically quote the equivalent aluminum thickness (mm Al Eq.)…”
Section: Discussionmentioning
confidence: 99%
“…The energy spectrum incident on the patient skin for under‐table exposures would therefore differ from those oriented in the lateral direction. DeLorenzo et al showed that the patient support attenuates the x‐ray beam and becomes a source of forward scatter, and some combinations of table and pad can reduce the transmission of air kerma to 60% of its original value . With the presence of the patient support in mind, we hypothesize that PSD calculations would benefit from measuring BSF and TTF simultaneously to produce a single value for x‐ray beam orientations that intercept the patient support.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The effect of the patient table and the mattress on the x‐ray beam transmission is taken into account by using italicTAF which depends on beam quality, field size, and C‐arm angulation. DeLorenzo et al 33 . found that italicTAF values at 0° for table plus pad ranged from 0.59 to 0.89 for three different fluoroscopy systems.…”
Section: Methodsmentioning
confidence: 99%
“…The data obtained should be corrected for the attenuation of the couch to get a more accurate estimation of the dose to the investigated phantom. Transmission factors for the couch of several angiographic devices was measured as reported in DeLorenzo et al 10 .…”
Section: Methodsmentioning
confidence: 99%